1994
DOI: 10.1159/000236797
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of the H<sub>1</sub> Antagonist Loratadine on Histamine Release from Human Basophils

Abstract: Loratadine is a powerful H1 antagonist commonly employed in the treatment of allergic disorders. The present study was performed to investigate whether loratadine, in addition to anti-H1 activity, is able to modulate histamine release from human basophils. Leukocyte suspensions were prepared by dextran sedimentation of peripheral venous blood drawn from 10 normal subjects. Leukocytes were stimulated with anti-IgE (1/5,000), N-formyl-methionyl-leucyl-phenylalanine (FMLP; 10 μM) and the Ca<… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 24 publications
3
11
0
4
Order By: Relevance
“…The inhibitory properties of rupatadine on MC degranulation are in agreement with those observed by several H 1 -antihistamines (e. g, terfenadine, cetirizine and azelastine) [1,14,22], although the exact mechanism of action remains unknown [22]. Miadonna et al [18], in a study with loratadine, suggested that it affects a common step implicated in biochemical events that provokes the cellular calcium influx, MC activation and exocytosis. Due to the chemical similarities and the inhibitory profiles of rupatadine and loratadine, we think that both compounds may act at the same level, although further studies on cytosolic Ca 2+ levels will be required to elucidate the mechanism.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The inhibitory properties of rupatadine on MC degranulation are in agreement with those observed by several H 1 -antihistamines (e. g, terfenadine, cetirizine and azelastine) [1,14,22], although the exact mechanism of action remains unknown [22]. Miadonna et al [18], in a study with loratadine, suggested that it affects a common step implicated in biochemical events that provokes the cellular calcium influx, MC activation and exocytosis. Due to the chemical similarities and the inhibitory profiles of rupatadine and loratadine, we think that both compounds may act at the same level, although further studies on cytosolic Ca 2+ levels will be required to elucidate the mechanism.…”
Section: Discussionsupporting
confidence: 76%
“…Now, we have examined the effects of rupatadine, in comparison to loratadine and SR-27417A, on histamine release from dog skin MC challenged with FceRI-dependent and -independent stimuli. Anti-IgE antibody induces mem- brane-IgE-cross linking, leading to aggregation of the FceRI receptors causing MC degranulation and histamine release [18]. Con A is a lectin that may directly cross-link FceRI receptors and trigger the degranulation process [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of the authors was that the inhibition of mediator release by loratadine may provide an additional action which contributes to its therapeutic effectiveness. More recently, similar results were obtained on human basophils (IC 50 of 30 mM on histamine release) [2]. The conclusion of the authors were more mitigated than in the previous paper.…”
Section: H 1 -Receptor Antagonists and Mast Cell/basophil: Search Forsupporting
confidence: 80%
“…The conclusion of the authors was that the inhibition of mediator release by loratadine may provide an additional action which contributes to its therapeutic effectiveness. More recently, similar results were obtained on human basophils (IC 50 of 30 μM on histamine release) [2]. The conclusion of the authors were more mitigated than in the previous paper.…”
Section: H1‐receptor Antagonists and Mast Cell/basophil: Search For Asupporting
confidence: 78%